2017
DOI: 10.1055/s-0037-1608629
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Venous Thromboembolic Complications after Microsurgical Breast Reconstruction

Abstract: Patients sustaining postoperative VTE after microsurgical breast reconstruction are more likely to have an increased volume of blood transfusions and lack of discharge on postoperative aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Three studies examined whether longer RBC storage times were associated with higher venous thrombosis rates. 27,44,45 None of these analyses showed statistically significant differences.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Three studies examined whether longer RBC storage times were associated with higher venous thrombosis rates. 27,44,45 None of these analyses showed statistically significant differences.…”
Section: Resultsmentioning
confidence: 87%
“…33,39,55 Some studies reported frequencies of drug anticoagulation in their patients. None of the seven studies with overall high-anticoagulation rates of 98 to 100% 26,27,35,39,43,47,49 had an MV-positive transfusion-thrombosis correlation, compared with 3 25,40,41 of 10 (30%) with anticoagulation rates of 0 to 75% or "rare" or "most." 25,29,31,36,38,40,41,[50][51][52] However, three of the high-anticoagulation studies still had UV-positive correlation with transfusion and/or correlation with transfusion volume.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations